The Nexus of Energy Supply and Human Health - Timilsina, Govinda R. (World Bank, Washington, DC, 2017)
Uses of main primary energy resources, such as coal, oil, and solid biomass, are directly linked with adverse impacts on human health. Air pollution emitted from various activities in the energy supply chains is the main risk factor to human health, along with accidental and occupational risk exposures. Estimates of premature deaths are over four million per year for ambient air pollution (2015) and household or indoor air pollution (2012). More than 80 percent of the mortality from ambient air pollution emitted from the energy supply chains occurs in developing countries. The impact of household air pollution, mainly from traditional biomass used for cooking and space heating, disproportionately falls on women and children under age five years. Acute respiratory infections, mainly caused by household air pollution, are one of the largest categories of deaths (64 percent) of children under age five years in developing countries. These statistics indicate the deep nexus between the energy supply chain and human health. Yet, the negative implications for human health from energy use often receive inadequate consideration. It is critically important to take account of these human health impacts in developing energy supply plans and energy policies in developing countries.